Actividades LÃºdicas â€œAprendo Jugandoâ€ Para Desarrollar La Motricidad Gruesa En Los NiÃ±os Y NiÃ±as Del Primer AÃ±o De EducaciÃ³n BÃ¡sica - Fernando, Bayas Machado RamÃ³n; Lucia, Chicaiza Sinchi Dina; Leopoldo, Ponce Bravo HernÃ¡n; Carlos, Bayas Machado Juan (European Scientific Journal, ESJ, 2017)
The purpose of this current research is to make and implement a didactic guide based on playful activities called â€œAprendo Jugandoâ€. This is in a bid to develop the gross motor skills on the first year basic education of boys and girls at Santa Mariana Educational Unit in Riobamba. The guide was organized through a schedule, and it contains games to influence the big muscles movements. The games are intended to reinforce the basic motor skills to evaluate the coordination of the body movements such as jump, match, and jumping on one foot. The sample incorporated 20 children chosen at random. The results were obtained through a direct observation and they were registered with an observation card that was applied before and after the development of the guide. An indicator table was used. Here, the indicators were statistically analyzed, especially the ones that allowed evaluating the hypothesis significance with the use of the students test. At the end of the research, it was concluded that the application of the didactic guide develops the gross motor skills. These evidences play an essential role in the childÂ´s life. As a result, it is recommended to use the guide in a permanent and continuous way because if a child develops the gross motor skills in an appropriate way, he would have confidence on himself. Above all, it will be easier for him to assimilate the basic fine motor skills.